The Amphibulimidae (Mollusca: Gastropoda: Orthalicoidea) from Colombia and adjacent areas - Borrero, Francisco J.; Breure, Abraham S.h. (Zootaxa, 2011)
The land snails of the family Amphibulimidae occurring within northwestern South America are critically examined and notes on their distribution are given. The total number of taxa discussed is 61 (7 Dryptus, 54 Plekocheilus); of these, four Colombian Dryptus and 32 Plekocheilus species are included. The following new species are described: Plekocheilus (P.) bigener, P. (P.) incognitus, Plekocheilus (Eurytus) camaritagua, P. (E.) labiosus, and P. (E.) paraguas. The following nominal taxa are now synonymized: Plekocheilus (P.) speciosus (Pfeiffer, 1854) = P. (P.) plectostylus (Pfeiffer, 1848); Plekocheilus (Eurytus) couturesi Ancey, 1900 = P. (P.) glandiformis (Lea, 1838); Plekocheilus (Aeropictus) latilabris (Pfeiffer, 1855) = P. (A.) succineoides (Petit de la Saussaye, 1840); Plekocheilus (Eurytus) virgatus (Pilsbry, 1935) = P. (E.) mabillei (Crosse, 1867) = P. (E.) pulicarius (Reeve, 1848). Also, Simpulopsis fulguratus Miller, 1878 is now considered a junior subjective synonym of Simpulopsis (Eudioptus) citrinovitrea (Moricand, 1836). For the following species, precise localities are given for the first time: Dryptus stuebeli (Martens, 1885), Plekocheilus (Aeropictus) cathcartiae (Reeve, 1848), P. (E.) cardinalis (Pfeiffer, 1853), P. (Eurytus) episcopalis auriformis (Da Costa, 1904), P. (E.) episcopalis corticosus (Sowerby, 1895), and P. (E.) lynciculus (Deville & Huppé, 1850). Newly recorded for the Colombian malacofauna are the following taxa: Plekocheilus (P.) couturesi (Ancey, 1900), P. (Eurytus) piperitus (Sowerby I, 1837). The following taxa are excluded from the Colombian fauna: Dryptus funckii (Nyst, 1843), Plekocheilus (Aeropictus) veranyi (Pfeiffer, 1848), Plekocheilus (Eurytus) jimenezi (Hidalgo, 1872).